A PEDAGOGICAL PERSPECTIVE ANALYSIS OF TURKISH GENERATION Z UNIVERSITY STUDENTS' VIEWS ON VIRTUAL ECOLOGIES AND AVATAR AS SELF-CONSCIOUSNESS AND SELF-PRESENTATION - Erdamar, Fatih Selim; Akpinar, Burhan; Kuloğlu, Ayşenur (My University, 2023)
This study aims to analyse the views of Turkish Generation Z higher education students with metaverse experience on virtual-digital ecologies, self-consciousness, virtual sense of self, and avatar. Conducted on 389 students studying at Fırat University, this study is based on a descriptive survey design. The research data collected with the survey developed in line with the methodology were analyzed using the licensed SPSS package program of Fırat University. While doing analyses, the researchers drew upon frequency and percentage, which are diagnostic statistical techniques, as well as the Chi-square test. The results obtained from the analyses are as follows: Turkish Generation Z higher education students partially differ from their global peers in terms of self-consciousness. Self-consciousness and the virtual sense of self of Turkish Generation Z higher education students are associated with reality-virtuality oscillation. These students view the avatar as an ideal profile self-presentation rather than a substitute for their real self. The following considerations were revealed based on the results: It can be envisaged that depending on the proliferation of the virtual-digital revolution on a global scale, the massiveness of the virtuality phenomenon is likely to increase in the self formation of Turkish Generation Z higher education students. The fact that the individual's self-consciousness and self-development are associated with the purpose, design, and practices of education requires Turkey to be ready for virtual-digital ecologies in education, at least as a contemporary complement to existing face-to-face education for now.
Keywords: Eğitim; Eğitim Araştırmaları